Pengembangan E-Modul Berbasis Android Berbentuk Flipbook pada Materi Sistem Ekskresi dan Sistem Koordinasi Untuk Peserta Didik Kelas XI SMA - Nanta Mulia; Linda Advinda; Syamsurizal; Yuni Ahda (Postgraduate, University of Mataram, 2024)
Increasingly developing technology encourages educators to use it in the learning process as a learning medium in order to increase student’s interest in learning. However, currently there are still many who do not optimally use technology-based learning media. The learning media used is monotonous and unable to visualize the material on the excretion system and coordination system in humans. This has an impact on student learning outcomes which are still below the school's Minimum Completion Criteria. Therefore, technology-based learning media such as e-modules in the form of flipbooks are needed. This research aims to produce an Android-based e-module in the form of a flipbook on excretion system and coordination system material that is valid, practical and effective. The type of research used is development research using the Plomp development model which consists of three stages, namely the initial investigation stage, the development stage (prototyping), and the assessment stage. The instruments used were teacher interview guide instrument sheets, student questionnaire sheets, self-evaluation sheets, and e-module validation sheets by experts, as well as e-module practicality assessment sheets in the form of flipbooks filled in by teachers and students. The subjects of this research were class XI high school students. The research object is an Android based e-module in the form of a flipbook on excretion system and coordination system material. The research results show that the Android based e-module in the form of a flipbook obtained very valid criteria validity results with a value of 86.76% and 89.06%, practicality results by teachers and students with very practical criteria with a value of 84.17% and 86.43%. Based on the T test carried out, there is a difference in value between the experimental class and the control class, namely a significance of 0.048 in the excretion system material and 0.003 in the coordination system material. Thus, Android-based e-modules in the form of flipbooks can improve students learning competence.